2017
DOI: 10.18632/oncotarget.16020
|View full text |Cite
|
Sign up to set email alerts
|

Increased platelet-lymphocyte ratio closely relates to inferior clinical features and worse long-term survival in both resected and metastatic colorectal cancer: an updated systematic review and meta-analysis of 24 studies

Abstract: Colorectal cancer (CRC) is one of the most common cancers worldwide. However, the prognostic and clinical value of platelet-lymphocyte ratio (PLR) in colorectal cancer was still unclear, which attracted more and more researchers considerable attention. We performed a systematic review and meta-analysis to investigate the relationship between PLR and survival as well as clinical features of CRC update to September 2016. The hazard ratio (HR) or odds ratio (OR) with 95% confidence interval (CI) were calculated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 54 publications
3
31
1
2
Order By: Relevance
“…Some pooled studies explored the prognostic role of PLR in CRC and reported that elevated PLR was significantly associated with poor prognosis [ 30 , 31 ]. Our study was based on the northern Chinese population and had some new findings.…”
Section: Discussionmentioning
confidence: 99%
“…Some pooled studies explored the prognostic role of PLR in CRC and reported that elevated PLR was significantly associated with poor prognosis [ 30 , 31 ]. Our study was based on the northern Chinese population and had some new findings.…”
Section: Discussionmentioning
confidence: 99%
“…Using lymphocytes and monocytes as surrogate markers of tumor microenvironment and inflammatory responses, more and more studies have found that elevated absolute monocyte count (AMC), decreased absolute lymphocyte count (ALC), and the absolute lymphocyte to absolute monocyte count ratio (LMR) are predictors of various solid tumors, such as breast carcinoma, ovarian cancer, clonal cancer, and lung cancer, and similar findings have also been demonstrated in diffuse large B‐cell lymphoma (DLBCL) and classical Hodgkin's lymphoma (cHL) . In addition, parameters such as neutrophil‐lymphocyte ratio (NLR) and platelet‐lymphocyte ratio (PLR) have also exhibited prognostic activity in recent studies, although there were conflicting results . In the present study, the role of LMR, NLR, and PLR in the setting of adult T‐LBL was first discussed.…”
Section: Introductionmentioning
confidence: 87%
“…Another extensively studied marker of systemic inflammation is PLR. Several publications state an association between elevated PLR and worse prognosis in CRC patients, namely, OS, CSS, disease-free and recurrence-free survival (50)(51)(52) in both localized and metastatic disease. There are several known mechanisms for increased PLR in cancer patients.…”
Section: Systemic Inflammation Markers In Crcmentioning
confidence: 99%